Safety, hemodynamic effects, and detection of acute xenon inhalation: rationale for banning xenon from sport - Lawley, J. S.; Gatterer, H.; Dias, K. A.; Howden, E. J.; Sarma, S.; Cornwell 3rd, W. K.; Hearon Jr., C. M.; Samels, M.; Everding, B.; Bruick, R. K.; Hendrix, M.; Piper, T.; et al. (Journal of Applied Physiology, 2019)
This study aimed to quantify the sedative effects, detection rates, and cardiovascular responses to xenon. On 3 occasions, participants breathed xenon (FiXe 30% for 20 min; FiXe 50% for 5 min; FiXe 70% for 2 min) in a nonblinded design. Sedation was monitored by a board-certified anesthesiologist. During 70% xenon, participants were also verbally instructed to operate a manual value with time-to-task failure being recorded. Beat-by-beat hemodynamics were measured continuously by ECG, photoplethysmography, and transcranial Doppler. Over 48 h postadministration, xenon was measured in blood and urine by gas chromatography-mass spectrometry. Xenon caused variable levels of sedation and restlessness. Task failure of the self-operating value occurred at 60-90 s in most individuals. Over the first minute, 50% and 70% xenon caused a substantial reduction in total peripheral resistance (P < 0.05). All dosages caused an increase in cardiac output (P < 0.05). By the end of xenon inhalation, slight hypertension was observed after all three doses (P < 0.05), with an increase in middle cerebral artery velocity (P < 0.05). Xenon was consistently detected, albeit in trace amounts, up to 3 h after all three doses of xenon inhalation in blood and urine with variable results thereafter. Xenon inhalation caused sedation incompatible with self-operation of a breathing apparatus, thus causing a potential life-threatening condition in the absence of an anesthesiologist. Yet, xenon can only be reliably detected in blood and urine up to 3 h postacute dosing. NEW & NOTEWORTHY Breathing xenon in dosages conceivable for doping purposes (FiXe 30% for 20 min; FiXe 50% for 5 min; FiXe 70% for 2 min) causes an initial rapid fall in total peripheral resistance with tachycardia and thereafter a mild hypertension with elevated middle cerebral artery velocity. These dose duration intervals cause sedation that is incompatible with operating a breathing apparatus and can only be detected in blood and urine samples with a high probability for up to ~3 h.